43 Global resuscitation alliance utstein recommendations for developing emergency medical services systems to improve cardiac arrest survival. (16th April 2018) - Gayathri, N; Tiah, L; Ho, AFW; Ajaz, A; Ohn, HM; Wong, KD; Wallis, LA; Leong, BS; Lippert, F; Castren, M; Ma, MHM; El Sayed, MJ; et al.
Abstract : Aim: The Global Resuscitation Alliance (GRA) 10 steps were established in 2015 to improve survival for Out-of-Hospital Cardiac Arrest (OHCA). However, these 10 steps were recommended mainly for developed Emergency Medical Services (EMS) systems and implementing these steps can be challenging for developing EMS systems. We aimed to explore barriers faced by developing EMS systems and to establish pre-requisites needed to improve survival. We also developed a framework for developing EMS systems to build their emergency response capability. Method: A consensus meeting was called in Singapore on 1 st and 2nd August 2017. There were 74 participants who were key stakeholders from 26 countries including EMS directors, physicians and academics. The group was subdivided into 4 groups to represent the chain of survival- community, dispatch, ambulance and hospital, with a separate group on perinatal resuscitation. Pertinent questions were given to the group for discussion, following which their answers were presented and voted upon to reach a consensus. Results: Each group's discussion points were used to construct the modified survival framework and create 11 key statements to describe the pre-requisites for achieving the GRA 10 steps. The participants then voted on the importance and feasibility of these 11 statements as well as the GRA 10 steps. Conclusion: In this paper, we propose a modified framework of survival for developing EMS systems. There are barriers for developing EMS systems to improve OHCA survival rates. These barriers may be overcome by systematic prioritisation and cost effective innovative solutions. Conflict of interest: None Funding: The consensus meeting was support by the Laerdal Foundation grant, grant no: 50 005